Age-related differences in fixation gaze length while reading the news with negative text elements - Ivaskevych, Daryna; Popov, Anton; Rizun, Volodymyr; Havrylets , Yurii; Petrenko-Lysak, Alla; Yachnik, Yuliia; Tukaiev, Sergii (East European Journal of Psycholinguistics, 2023)
The worldwide COVID-19 pandemic has led to the development of stress disorders and increased societal anxiety. The mass media is one of the most decisive factors leading to anxiety and stress in society during a pandemic. However, the mechanisms of mass media’s stressogenic effects remain unclear. This study aimed to evaluate age-specific characteristics of gaze behavior related to the perception of anxiety-provoking information. One hundred eighty-nine volunteers took part in the study – 164 participants aged between 17 and 22 years old (students, control group), 25 people aged between 59 and 71 (experimental group). We surveyed participants to determine their level of stress, depression, and anxiety and analyzed eye-tracking data during text perception by using the web eye-tracking technology EyePass. Results showed significant age-related differences in gaze behavior while reading texts with negative elements. Aged adults had shorter median fixation duration. There was no difference between groups in the number of fixations. We can assume that except age factor, other variables might have contributed to our result, namely the occupation of participants, professors at the Scientific and Educational Institute of Journalism, with developed professional skills (reading pattern, method of information perception) but from another side higher vulnerability to adverse COVID-19 outcomes compared to younger adults. Acknowledgements The authors of this article express their sincere gratitude to the National Research Foundation of Ukraine, thanks to whose financial and organizational support (grant “Stressogenic Elements of the Latent Impact of Real Media Reports on the COVID-19 Pandemic on Social Groups” No. 2020.01/0050), it became possible to conduct this study and publish the experimental results. Words of gratitude to the management and Scientific Council of the Foundation, curators of the project. Vast gratitude to the experts for their high evaluation of our project, thanks to whom our application won the competition. We want to express particular thanks to the management and our colleagues fromTaras Shevchenko National University of Kyiv, whose care and assistance contributed to the effective work within the project. Words of gratitude to colleagues and students who agreed to participate and actually contributed to the timely collection and processing of the experimental data. Disclosure Statement No potential conflict of interest was reported by the authors. Data Availability Statement The data that support the findings of this study are openly available in Mendeley Data https://doi.org/10.17632/rpytj9dkmx.3 * Corresponding author: Yurii Havrylets, 0000-0002-4899-5815 havrylets@knu.ua